2010
DOI: 10.1111/j.1472-8206.2010.00861.x
|View full text |Cite
|
Sign up to set email alerts
|

Dose response effect of rutin a dietary antioxidant on alcohol-induced prooxidant and antioxidant imbalance - a histopathologic study

Abstract: The present study was designed to investigate the effect of rutin on ethanol-induced hepatotoxicity in a dose-dependent manner in rats. Male albino rats were divided into six groups. Group 1 rats served as control and group 2 rats received rutin 100 mg/kg body weight. Hepatotoxicity was induced in groups 3-6 rats (20% ethanol) for 60 days. In addition, groups 4-6 rats received rutin at doses of 25, 50, 100 mg/kg body weight, respectively for the last 30 days of the experiment. We observed a significant increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
18
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 46 publications
4
18
2
Order By: Relevance
“…We believe that these effects are through the additive hepatoprotective effects of both vitamins. These findings are in accordance with other investigations, where both RT and AA were found to prevent hepatotoxicity and hepatic injury in different animal models (Abhilash et al, 2012;Banerjee et al, 2009;Janbaz et al, 2002;Rana et al, 2010;Shenbagam and Nalini, 2011). Both RT and AA are well recognized to protect against free radicals induced tissue damage through several biological processes in many extracellular and intracellular reactions (Mahmoud, 2011;Ozkaya et al, 2011).…”
Section: Discussionsupporting
confidence: 92%
“…We believe that these effects are through the additive hepatoprotective effects of both vitamins. These findings are in accordance with other investigations, where both RT and AA were found to prevent hepatotoxicity and hepatic injury in different animal models (Abhilash et al, 2012;Banerjee et al, 2009;Janbaz et al, 2002;Rana et al, 2010;Shenbagam and Nalini, 2011). Both RT and AA are well recognized to protect against free radicals induced tissue damage through several biological processes in many extracellular and intracellular reactions (Mahmoud, 2011;Ozkaya et al, 2011).…”
Section: Discussionsupporting
confidence: 92%
“…Similar results were obtained by Shenbagam and Nalini (2011) who reported that supplementation of rutin along with ethanol significantly decreased the levels of liver marker enzymes, lipidperoxidation and significantly elevated the activities of liver SOD, CAT, GSH, glutathione peroxidase, vitamins C and E when compared to untreated ethanol supplemented rats. Rutin possesses a unique ability to inhibit free radical processes in cells at three different stages: an initiation (by the interaction with superoxide ion), the formation of hydroxyl or radicals (by chelating iron ions) and lipid peroxidation (by reacting with lipid peroxy radicals).…”
Section: Discussionsupporting
confidence: 77%
“…The possible explanation for this is that apart from the free radicals mediated depletion of ascorbic acid in hepatitis; alcohol directly reduces ascorbic acid levels in blood by impairing its absorption, disabling transport into the blood, and altering vitamin C metabolism and utilization. [11–13] The measure of liver enzymes revealed a significant rise in the levels of AST ( P < 0.005), ALT ( P < 0.005), ALP ( P < 0.005) and GGT ( P < 0.005) in both hepatitis B virus infection and alcoholic hepatitis, compared with controls, which also confirms the literature evidence. [14–16] The AST/ALT ratio was found to be < 1 in controls as well in hepatitis B, but > 1 in alcoholic hepatitis patients.…”
supporting
confidence: 77%